2018
DOI: 10.3389/fimmu.2018.02776
|View full text |Cite
|
Sign up to set email alerts
|

The Yin and Yang of Myeloid Derived Suppressor Cells

Abstract: In recent years, most of our knowledge about myeloid derived suppressor cells (MDSCs) has come from cancer studies, which depicts Yin side of MDSCs. In cancer, inherent immunosuppressive action of MDSCs favors tumor progression by inhibiting antitumor immune response. However, recently Yang side of MDSCs has also been worked out and suggests the role in maintenance of homeostasis during non-cancer situations like pregnancy, obesity, diabetes, and autoimmune disorders. Continued work in this area has armored th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 170 publications
3
46
0
Order By: Relevance
“…However, high-dose ablative IR reduced the level of MDSCs (22). We found the same results in two HCC tumorbearing mouse models: (1) the higher the IR dose/fraction, the bigger the off-target effect (Figure 2); (2) the bigger the tumor, the higher the blood MDSCs (both G-MDSCs and M-MDSCs) (C-E) The bone marrow cells were harvested from C57BL/6 or Institute of Cancer Research (ICR) mice and co-cultured with CM from Hepa1-6 or H22 cells irradiated with different single doses (0, 2.5, 4, 6, or 8 Gy). Three days later, the differentiation of the bone marrow cells into MDSCs or their proliferated was monitored by CD11b/Gr1 staining or 5,6-carboxyfluorescein diacetate (CFSE) assay.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…However, high-dose ablative IR reduced the level of MDSCs (22). We found the same results in two HCC tumorbearing mouse models: (1) the higher the IR dose/fraction, the bigger the off-target effect (Figure 2); (2) the bigger the tumor, the higher the blood MDSCs (both G-MDSCs and M-MDSCs) (C-E) The bone marrow cells were harvested from C57BL/6 or Institute of Cancer Research (ICR) mice and co-cultured with CM from Hepa1-6 or H22 cells irradiated with different single doses (0, 2.5, 4, 6, or 8 Gy). Three days later, the differentiation of the bone marrow cells into MDSCs or their proliferated was monitored by CD11b/Gr1 staining or 5,6-carboxyfluorescein diacetate (CFSE) assay.…”
Section: Discussionsupporting
confidence: 74%
“…Myeloid derived suppressor cells (MDSCs), a group of highheterogeneity immune-negative regulating cells, have two subgroups: granulocytic MDSC (PMN-MDSC) and monocytic MDSC (M-MDSC) with their own functions (1). In pathological conditions (such as an infection and an autoimmune disease), overproduced inflammation molecules and overstimulated proliferation, and differentiation of immune cells could be restrained by MDSCs to keep the reaction under control and to balance immune response and host's homeostasis (2).…”
Section: Introductionmentioning
confidence: 99%
“…M-MDSCs produce high amounts of NO, Arginase I (Arg-1), and immunosuppressive cytokines, such as IL-10, which suppress both antigen-specific and nonspecific T-cell responses. Mo-MDSCs are more potent suppressors than PMN-MDSCs because of NO, which has a longer half-life than ROS and reacts at greater distances [12]. A study revealed that Mo-MDSC (CD14 + HLA-DR −/low ) fractions were elevated in psoriasis patient peripheral blood mononuclear cells (PBMCs) compared to healthy controls, and, importantly, regulatory T cells induced by psoriasis Mo-MDSCs displayed decreased suppressive functionality [13].…”
Section: Introductionmentioning
confidence: 99%
“…1 Considerable evidence has now been accumulated from the work previously reported by our group and others that a group of heterogeneous, immature cells of myeloid origin referred as myeloid-derived suppressor cells (MDSCs) is master regulator of many immune and nonimmune functions during early pregnancy. 3 These cells display both Yin and Yang behavior.…”
Section: Introductionmentioning
confidence: 99%
“…These cells display both Yin and Yang behavior. 3 Role of MDSCs was first shown in pathological settings such as cancer, sepsis, trauma where differentiation of these cells gets blocked and this blockage of differentiation leads to compromised immunity and favors progression of diseased state. 4,5 Interestingly, our group because of immunosuppressive nature of MDSCs is interested to explore the YANG side of these cells particularly its role in maternal-fetal tolerance.…”
Section: Introductionmentioning
confidence: 99%